Identification of ripening-related genes in strawberry fruit by cDNA-AFLP - Balogh, A.; Koncz, T.; Tisza, V.; Kiss, E.; Heszk, L. (International Journal of Horticultural Science, 2005)
An RNA fingerprinting study of strawberry receptacle and achene tissue was performed to identify candidate genes involved in fruit ripening. Quantitative cDNA-AFLP was used to detect differential gene expression in green, white, pink and red stages of fruit ripening. Based on hierarchical average linkage clustering the differentially expressed genes formed three major groups, genes expressed only in green receptacle, genes expressed mainly in white, pink and red receptacle, and in achene. 130 transcript-derived fragments (TDFs) were isolated and sequenced. Most TDFs did not show any homology to sequences with known functions, others were homologous to genes involved in oxidative stress response, signal transduction, regulation of development and cell-wall metabolism. Novel genes, so far not associated with strawberry ripening and ripening in general, were identified, such as genes encoding a bHLH protein, putative nitrilase-related protein, putative HD-zip protein. The differential pattern of gene expression draws the attention to the significance of ripening induced-or repressed promoters in strawberry fruit, whose isolation and characterization can be useful tool for functional genomics. For this purpose nine cDNA-AFLP fragments related either to ontogeny or senescing were completed with 5’UTR aiming at more precise annotation and future promoter isolation. Although tens of potentially important transcriptome changes were identified, the function of many ripening induced genes remain unknown.